2010
DOI: 10.1523/jneurosci.3310-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic BDNF Promotes Postsynaptic Long-Term Potentiation in the Dorsal Striatum

Abstract: Brain-derived neurotrophic factor (BDNF) facilitates the formation of long-term potentiation (LTP) in hippocampus, but whether this involves release from presynaptic versus postsynaptic pools is unclear. We therefore tested whether BDNF is essential for LTP in dorsal striatum, a structure in which the neurotrophin is present only in afferent terminals. Whole-cell recordings were collected from medium spiny neurons in striatal slices prepared from adult mice. High-frequency stimulation (HFS) of neocortical affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 43 publications
(50 reference statements)
3
77
0
Order By: Relevance
“…Furthermore, MARK induces hippocampus granular cells to produce continuous long-term potentiation (LTP) (Kobayashi et al 2006), which is currently recognized as the neural basis for learning and memory. The influences of BDNF on learning and memory are mainly due to the regulatory effects of BDNF on LTP (Jia et al 2010). In our study, BDNF expression in the PND7 newborn rats in the M group was significantly lower than the N group, which suggests that the relative thyroid hormone deficiency in female rats with marginal iodine deficiency has a negative impact on BDNF and can further influence the brain development of offspring.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, MARK induces hippocampus granular cells to produce continuous long-term potentiation (LTP) (Kobayashi et al 2006), which is currently recognized as the neural basis for learning and memory. The influences of BDNF on learning and memory are mainly due to the regulatory effects of BDNF on LTP (Jia et al 2010). In our study, BDNF expression in the PND7 newborn rats in the M group was significantly lower than the N group, which suggests that the relative thyroid hormone deficiency in female rats with marginal iodine deficiency has a negative impact on BDNF and can further influence the brain development of offspring.…”
Section: Discussionmentioning
confidence: 52%
“…This shift in iSPNs could reflect a homeostatic adaptation to a reduction in the strength or number of glutamatergic synapses following TrkB deletion. Consistent with this conjecture, BDNF and TrkB signal- ing enhanced LTP induction at glutamatergic synapses on striatal SPNs (42) and, thus, their downregulation in HD would be expected to impair LTP (43,44), as described in other regions (45,46). This could prevent cortical neurons from effectively activating iSPNs to suppress unwanted activity.…”
Section: Hd Pathogenesis Is Rooted In Network Dysfunctionmentioning
confidence: 53%
“…Previous studies have shown that theta-burst stimulation induces the release of endogenous BDNF from mossy fibers, as well as Schaffer collaterals onto the dendrites of CA3 and CA1 pyramidal neurons, respectively, and this mediates long-lasting changes in potentiation or depression (3,48,6,49). Moreover, a recent study demonstrated that release of BDNF from cortical axons onto dendrites of medium spiny neurons in the dorsal striatum induced postsynaptic LTP (50). It is conceivable that dendritically derived BDNF-TrkB endosomes have a role in these pathways.…”
Section: Discussionmentioning
confidence: 96%